Complicated Work as Goal of Higher Education - V. A. Galanov; A. V. Galanova (Вестник Российского экономического университета имени Г. В. Плеханова, 2024)
Robotization of goods production and service rendering means the necessity of gradual transition to training specialists of new profiles characterized by increasing complexity of work. Material sphere, as production robots are introduced in it will change into the sum total of fields of complicated work application, which include engineering of consumer goods, constructing of robots, technical science and economic management. Complicated work turns into qualified work relying on possibilities of artificial intellect. Training for complicated work implies the necessity for the person to get the ability to deal with new types of activity and to cope with them. In this way the person himself/herself turns into the subject of such work. In this aspect the article shows that complicated work covers social and spiritual fields of a new specialist formation: education and up-bringing relying on achievements of social science and on art. The authors came to the conclusion that introducing artificial intellect in processes of the man moulding will allow him/her to overcome personal limits for upgrading and learning complicated work impossible for robots.